INAA to determine trace element concentrations in the hair of street children of Isfahan city, Iran - Saraee, Khadijeh Rezaee Ebrahim; Abdi, Mohammad Reza; Gharipour, Mohammad Mehdi; Soltani, Nayereh (Scientific Research Publishing, 2013)
This study aimed to assess trace element concentrations in the hair of street children. Nutritional status was assessed by 24 hours’ dietary recall and anthropometric measurements. Data analysis found that Br, Sc, Sm and Ti concentrations show a normal distribution, and there is no significant difference between street children and control group. However, in the street children’s hair, the levels of Au, U, V are decreased and the levels of Co, La, Sb, Th are increased compared to the control group.